2017
DOI: 10.5007/2175-8077.2017v19n48p96
|View full text |Cite
|
Sign up to set email alerts
|

Family Owned Business Succession and Governance: a multiple case study in Brazil

Abstract: One of the main threats to the continuity of family-owned business is the poor management of the succession process between generations of the family. This risk factor can be avoided when the process works properly and can also become a renewal and strengthening tool for organizations. The aim of this study is to evaluate the different factors that trigger the succession, as well as the various ways in which companies act and react to the process and the succession's turbulence. The methodology used was a qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 7 publications
(7 reference statements)
0
11
0
7
Order By: Relevance
“…With the transfer of leadership to a non-family member, i.e., a transfer of management, the company remains a family business, as there is no transfer of ownership. In this sense, when planning, some strategies, such as managerial professionalization, family governance, and the creation of holdings, can lead to better results (Roth et al, 2017).…”
Section: Succession and Life Cycle In Family Businessesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the transfer of leadership to a non-family member, i.e., a transfer of management, the company remains a family business, as there is no transfer of ownership. In this sense, when planning, some strategies, such as managerial professionalization, family governance, and the creation of holdings, can lead to better results (Roth et al, 2017).…”
Section: Succession and Life Cycle In Family Businessesmentioning
confidence: 99%
“…Succession, thus, is characterized as a relevant moment in the life of the family business and implies changes in management due to the impact on the activities resulting from command change (Roth, Tissot, & Gonçalves, 2017). In this sense, it can be an opportunity to improve the management of the company as it is a time of renewal and strengthening for organizations (Roth et al, 2017) based on the challenges imposed that require strategies to act differently (Oro & Lavarda, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conflict is part of the nature of the family business (Roth et al, 2017). In these companies, emotions and feelings of affection for the business are present (Carmon, Miller, Raile, & Roers 2010;Spranger, Colarelli, Dimotakis, Jacob, & Arvey, 2012).…”
Section: Conflict In Succession In Family Businessesmentioning
confidence: 99%
“…This definition provides a complete and integrative view of two elements, as follows: (1) A structure-based element related to family involvement in firm ownership and management and (2) an intention-based element concerning values and preferences of family firms and their intention to keep the business in the family. Since then, considerable research on FOBs has focused on succession, which has often been identified as a key topic that merits the attention of both researchers and family businesses themselves [3][4][5][6]. Surprisingly, however, most studies of succession in FOBs are based on the theory of planned behavior, which encourages a managerial and procedural focus [7][8][9].…”
Section: Introductionmentioning
confidence: 99%